RUBU’ MUJAYYAB SEBAGAI ALAT HISAB RASHDUL KIBLAT - Indraswati, Lutfi Nur Fadhilah (Ahkam: Jurnal Hukum Islam, 2020)
This research discusses daily reckoning of the Qibla with rubu’ mujayyab. A special discussion about the shadows of the Qibla using rubu’ mujayyab also does not yet exist in the classic books that examine rubu’ mujayyab. The discussion only reaches the determination of the Qibla direction. The study employs library research that is descriptive comparative.The results of the study show first, that the daily qibla method of reckoning with rubu’ mujayyab can be categorized as classic reckoning because it uses data and calculating devices which are classified as classic tools. However, the theory and system of calculation is based on the modern astronomical formula using rubu’ mujayyab. The shadow calculation of this Qibla does not use the place longitude and the equation of time, so the result of the calculation is istiwa’ time. Secondly, the accuracy of the shadows of Qibla with rubu’ mujayyab when compared to contemporary reckoning methods using ephemeris data and scientific calculators shows a difference of 1-4 minutes.